2020
DOI: 10.1002/agj2.20135
|View full text |Cite
|
Sign up to set email alerts
|

Cover crop impact on irrigated cotton yield and net return in the southern Great Plains

Abstract: Cover crops have the potential to increase ecosystem services of cropping systems, although mixed results have been found throughout the U.S. Great Plains. Crop performance and economic returns are often used by producers to gauge the feasibility of adoption. In addition, soil moisture use by cover crops is a concern in semiarid environments. The objective of this research was to determine the impact of cover crops on cotton (Gossypium hirsutum L.) yield and economic return compared with conventional practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In wetter regions, cover crops can be used to dry the soil to create suitable conditions for planting (Bronick & Lal, 2005), but cotton producers in relatively dry regions are concerned about yield loss due to cover crop moisture consumption. Previous reports on the systems we studied showed that there were no differences in stored soil moisture among systems during the cotton growing season (DeLaune, 2015; DeLaune et al., 2020), indicating that improved moisture infiltration and retention offset cover crop moisture consumption. Consistent with this, Adhikari et al.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In wetter regions, cover crops can be used to dry the soil to create suitable conditions for planting (Bronick & Lal, 2005), but cotton producers in relatively dry regions are concerned about yield loss due to cover crop moisture consumption. Previous reports on the systems we studied showed that there were no differences in stored soil moisture among systems during the cotton growing season (DeLaune, 2015; DeLaune et al., 2020), indicating that improved moisture infiltration and retention offset cover crop moisture consumption. Consistent with this, Adhikari et al.…”
Section: Discussionmentioning
confidence: 70%
“…Year‐to‐year yields of the cotton crops for the long‐term study in which this research took place are available in a recently published report (DeLaune et al., 2020). Relevant yields are given here for simpler reference.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from field experiments have been widely used to conduct economic analysis on alternative conservation practices (Boyer et al., ; Cochran, Roberts, Larson, & Tyler, ; Ott & Hargrove, ). In this study, a field experiment was conducted at Texas A&M AgriLife Research Station at Chillicothe, Texas (34°15′11.40″ N, 99°30′26.39″ W) from 2013 to 2018 (DeLaune, Mubvumba, Fan, & Bevers, ). Continuous cotton under irrigation was grown on a Rowena clay loam soil.…”
Section: Methodsmentioning
confidence: 99%